An examination of the use and value of support systems for people living with HIV/AIDS in Makhanda - Gorham, Catherine Margaret (Rhodes University, Faculty of Humanities, Department of Sociology)
Through the experiences of five people, this study asks how support systems develop, are used and are valued for those faced with the everyday challenges of living with HIV. Additional evidence is found in accounts from those identified as essential sources of support. These are primarily friends, sometimes family. This perspective is rounded out by insights gathered from those working in local organisations and in the analysis of services offered by the state. The three women and two men at the centre of this study live in Makhanda in the Eastern Cape, South Africa. Makhanda (formerly Grahamstown) is characterised by extremes of poverty and wealth, reflected in low employment, expanding informal and low-income settlement areas but also in a high level of community activism and access to resources. Each of the five tested positive for HIV variously between 1998 and 2008. These years were pivotal in the development of the local and national epidemic. The rapid expansion of infection rates, contestation over forms of and access to treatment, followed by emphasis of a biomedical response, in equal measure bracket and cut across their experiences. To this point, research is less concerned with what individual experiences say about living through the HIV/AIDS epidemic. Preoccupations lie more generally with macro- or micro-level factors, with behaviour change, managing risk and so public health "“ not the processes linking individual circumstances and choices to opportunities and outcomes described by individual, community and structural, socio-economic contexts. Personal accounts and observations of a developing, community-based, local response to an unfolding epidemic are therefore considered against the analysis of available medical and nonmedical resources. This enables identification and investigation of social processes operating between proximal and distal conditions, determining possibilities for access to support. The focus of this study thus falls to the interrelations of structure, agency and action. It contributes to an empirical and theoretical understanding of what "support" is, what "coping" means and what unfolds where diagnosis with HIV disrupts and challenges existing ways of coping and forms of support. The accounts gathered for this study offer an "insider" perspective, focused on what follows from testing positive to identifying what resources hold significance. Connections between individual, community and society, through psycho-social, local and macro-level processes are explored. Along with the empirical study of individual accounts, the thesis offers a theoretical framework that uses a grounded-theory approach in conjunction with the tools of narrative analysis. These are critically adapted from a sociology of illness studies. Ideas of risk and response, of material and social capital, of the nature of HIV/AIDS as an experience that is inclusive of both chronic, everyday challenge and critical, life-threatening crisis disrupting a sense of time, biography and self, are brought together in the analysis. In this way the understanding of what support means, how it develops and is used (systematically or not), and of the links operating between structural and social conditions, individual agency and action, can be developed. What the thesis finds is that, beyond the medical system of hospitals and clinics, there is surprisingly little use of available resources. There is thus an absence of any systematic support for those faced with the physical, psychological, social and material impacts of HIV/AIDS. Given the nature of personal circumstances, embedded as they are within local conditions that reflect structural constraints of the broader economy and society, this should not be surprising. A system of support exists in only the most limited definition. Against this, what is novel in these findings is the role that psycho-social processes play in negotiating these conditions and how this works, determining what unfolds. A key finding is that it is more through chance than choice that people do find conventional forms of support. The reasons for this have to do not only with limitations to state and institutional capacity, but also with the impact on individuals of perceptions of themselves shaped by the impact of the epidemic and also the past. The result is that under the burden of HIV/AIDS, in the context of extreme inequalities and the absence of an adequate response from the state, already invisible individuals who do not "count" run the risk of becoming doubly invisible. It is through a process of personal adaptation in which shifts in identity and a sense of self are key that they must find their own way. This involves re-conceptualisations of identity, a sense of self and place in the world. The focus on five people and the community in which they live is a limit to the scope of study Yet it is this focus which allows for a new understanding of the social processes involved, and so the links operating between individuals and society. This is of significance beyond the study of HIV/AIDS alone, contributing to the broader sociological project of understanding what it means to "be human" .
Keywords: HIV-positive persons -- South Africa -- Makhanda; AIDS (Disease) Patients -- South Africa -- Makhanda; Social networks; Diseases Social aspects; Health services accessibility; Narrative